Molecular mechanisms for the modulation of blood pressure and potassium homeostasis by the distal convoluted tubule - María Castañeda‐Bueno; David H Ellison; Gerardo Gamba (EMBO Molecular Medicine, 2021)
Abstract Epidemiological and clinical observations have shown that potassium ingestion is inversely correlated with arterial hypertension prevalence and cardiovascular mortality. The higher the dietary potassium, the lower the blood pressure and mortality. This phenomenon is explained, at least in part, by the interaction between salt reabsorption in the distal convoluted tubule (DCT) and potassium secretion in the connecting tubule/collecting duct of the mammalian nephron: In order to achieve adequate K+ secretion levels under certain conditions, salt reabsorption in the DCT must be reduced. Because salt handling by the kidney constitutes the basis for the long‐term regulation of blood pressure, losing salt prevents hypertension. Here, we discuss how the study of inherited diseases in which salt reabsorption in the DCT is affected has revealed the molecular players, including membrane transporters and channels, kinases, and ubiquitin ligases that form the potassium sensing mechanism of the DCT and the processes through which the consequent adjustments in salt reabsorption are achieved.